Thermal Analysis of Power Transformer; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Kravchenko E. V. Evgeny Vladimirovich (2015, 2015)
Title screen